Using Email Communication to Increase Expatriate Parents’ Knowledge of the Human Papillomavirus - Melissa M. Baker; Ratana Somrongthong (Intelektual Pustaka Media Utama, 2016)
Expatriates face a unique set of determinants to health which may influence their level of knowledge, perception of available preventative health care alternatives and their health seeking behaviors. The objective of this study is to understand the effect of an email communication intervention on expatriate parents’ level of knowledge of the Human Papillomavirus (HPV). Repeated measurement of knowledge was conducted pre- and post-intervention among parents who received the study intervention (group 1) and those who received standard care (group 2). Intervention effect was measured by any change in knowledge within and between groups. The group 1 had a significant rise in knowledge mean from baseline to first and then second follow-up (m = 0.57 (SD 0.39), m = 0.84 (SD 0.16) and m = 0.87 (SD 0.11), respectively). In addition, after receiving the intervention, group 1 felt they had sufficient information to make an informed decision of whether to vaccinate their child(ren), with a significant difference from baseline to first post test, (χ² (1) = 8.50, p < 0.05). Based on an increase in knowledge, the study’s email intervention proved effective mode to disseminating HPV-related information.